Effectivity of Holothuria scabra and Spirulina platensis extract combination as an Antiinflammatory Agent Measured by Carrageenan-induced Rat Paw Edema - Renni Yuniati; Bambang Sulardiono (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2020)
Sea cucumber, Holothuria scabra, can be found abundantly in Indonesian seas, which is also known to possess several medicinal properties. Spirulina platensis is another marine resources that has recently been extensively researched for its medicinal ability, such as anti-inflammatory effect. This study aims to evaluate the efficacy of H. scabra extract combined with S. platensis extract in reducing inflammation. This study uses male Wistar rats as the study animal. Inflammation was induced by injecting carrageenan solution into the mice paw. Combination of H. scabra and S. platensis extract with various combination ratio (1:1; 1:2; and 2:1) was applied to the mice paw. Diclofenac sodium was used as the standard control therapy. Edema inhibition rate and anti-inflammatory efficacy were measured by analyzing the edema size and calculating the edema difference. Combination of H. scabra and S. platensis with 1:1 ratio has the largest edema inhibition volume compared to the other treatments. H. scabra and S. platensis combination outperforms the positive diclofenac sodium control group in terms of edema inhibition. The highest anti-inflammatory effect is obtained in the combination of H. scabra and S. platensis with 1:2 ratio, however, the anti-inflammatory efficacy is not as potent as the positive control. The effectivity of Holothuria scabra and Spirulina platensis extract in reducing the edema might be caused by their ability to reduce the levels of several inflammatory markers, including IL-6, NO, MMP9, and COX-2. This result suggests that H. scabra and S. platensis combination has anti-inflammatory effect shown in mice paw edema model.